Stupanje u razgovor religije s prirodnom znanošću i teorijom evolucije / Religion entering a dialogue with natural sciences and the theory of evolution: primjer Katoličke crkve / an example of the Catholic Church - Isanović, Nusret (Context: Journal of Interdisciplinary Studies, 2022)
The first part of the paper is about the challenges that modern natural sciences, the theory of evolution and their increasingly numerous technological ecstasies pose before religion, about the attempts of religion to recognise them, make itself aware of their meaning and to respond to them, which is shown here on the example of the Catholic Church. The rest of the paper develops a discourse about the process of opening and the effort of entering the dialogue on the part of the Catholic Church with natural sciences and the theory of evolution, as well as about its official positions released from the mid-20th century, or from the papacy of Pius XII, till this day. At the same time, this period saw the rise of religious theistic evolutionism, recognised as one of the most appropriate forms of bringing religion closer to natural sciences and the theory of evolution, as well as a certain compromise between them, which this paper also tries to make transparent.